Selection of intervention areas for improving travel condition of walk-accessed bus users with a focus on their accessibility: An experience in Bhubaneswar. (September 2020) - Roy, Subhojit; Basu, Debasis
Abstract: The article presents an investigation into selection of priority areas of intervention for improving travel condition of walk-accessed bus users within a bus stop catchment area. The work considers that propensity to use bus service by walk-accessed bus users is bi-directionally elastic to both the quality of walk-access facility, and the service characteristics of bus operation. In view of this, the current work attempts to consider two lists of attributes each from walk-accessed facility and from service characteristics of bus operation, and then users' opinions on them are recorded in terms of perceived importance and satisfaction. The intervention areas are then identified by employing a two-dimensional analysis called Revised Importance Performance Analysis (R-IPA) using fuzzy-C means clustering. In this process, the factor structure and management scheme of the attributes are identified, and the list of intervention areas are finalized by comparing them. The attributes related to walk-access facility such as surface quality of sidewalk, interval between crosswalks, presence of dedicated sidewalk facility with adequate width, provision of adequate street lights and road surveillance are found to warrant immediate intervention. Similarly, the attributes related to service characteristics of bus operation such as frequency of bus service, in-vehicle journey time, and bus fare are also found to warrant immediate intervention. Highlights: Areas of intervention for improving travel condition of walk-accessed bus users. Travel condition bi-directionally elastic to walk-access facility and bus service. Two-dimensional approach considering users' perceived importance and satisfaction. Clusters for factor structure and management scheme obtained using Fuzzy C means. New evidences are observed with reference to urban area of developing country.